2001
DOI: 10.1161/01.cir.103.23.2799
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation Improves Endothelial Function in Patients With Coronary Artery Disease

Abstract: Deferoxamine improved nitric oxide-mediated, endothelium-dependent vasodilation in patients with coronary artery disease. These results suggest that iron availability contributes to impaired nitric oxide action in atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
139
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(152 citation statements)
references
References 42 publications
9
139
0
4
Order By: Relevance
“…In the clinical setting, sequestering free iron released during cold storage is possible, and such a strategy may prove to be useful as suggested by our work in the rat transplant model (25). Although iron chelators including deferoxamine have been used in a number of clinical studies (13,40,58,73), no published studies to our knowledge have addressed the efficacy of similar agents in cold ischemic injury of human organs removed for transplantation. While deferoxamine's protective effect that we found in the transplant model against cold is considered mainly due to its antioxidant properties (25), other effects of deferoxamine such as upregulation of cytoprotective genes, HO-1, EPO, and VGEF via HIF-I transcription factor are to be (3,76).…”
Section: Free Iron Release During Cold Storage: a Clinically Addressamentioning
confidence: 98%
“…In the clinical setting, sequestering free iron released during cold storage is possible, and such a strategy may prove to be useful as suggested by our work in the rat transplant model (25). Although iron chelators including deferoxamine have been used in a number of clinical studies (13,40,58,73), no published studies to our knowledge have addressed the efficacy of similar agents in cold ischemic injury of human organs removed for transplantation. While deferoxamine's protective effect that we found in the transplant model against cold is considered mainly due to its antioxidant properties (25), other effects of deferoxamine such as upregulation of cytoprotective genes, HO-1, EPO, and VGEF via HIF-I transcription factor are to be (3,76).…”
Section: Free Iron Release During Cold Storage: a Clinically Addressamentioning
confidence: 98%
“…Accordingly, benefit may be derived from iron chelation. Fifteen years ago, it was shown that iron chelation improves endothelial function in patients with coronary artery disease [10]. Deferoxamine improved nitric-oxidemediated, endothelium-dependent vasodilation, suggesting that iron availability contributes to impaired nitric-oxide action in atherosclerosis.…”
Section: Clinical Consequences Of Iron Overload In Mdsmentioning
confidence: 99%
“…161 Finally, when patients with coronary artery disease and control patients were infused with DES (500 mg during 1 h), a significant drop in serum iron concentrations was observed. 162 In addition, a significant increase in resting forearm blood flow was noted immediately after the start of infusion in both groups, and it persisted for the entire period of infusion.…”
Section: Iron-related Neurotherapeuticsmentioning
confidence: 83%